Meningkatkan Hasil Belajar dengan Metode PBL Berbantuan Video Fase E Kelas X SMK Negeri 2 Pontianak - Marina Yulita; Nerita Setyaningtyas; Tarsisius Adi Prasetya (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Effective and innovative education is the key to improving student learning outcomes, especially in today's digital era. At SMK Negeri 2 Pontianak, class X phase E faces challenges in understanding the material Suara Hati and Bertanggungjawab, with many students having difficulty due to the dominant lecture method and the lack of adequate learning facilities. This study proposes the implementation of the video-assisted Problem Based Learning (PBL) method, which can encourage students to think critically and be actively involved in the learning process. This method is expected to enrich the learning experience and increase student motivation. Through classroom action research conducted in two cycles, the results showed that the implementation of video-assisted PBL succeeded in improving student learning achievement from 50% in the first cycle to 80% in the second cycle. Students' critical thinking skills also increased from 60% to 90% in the same period. These findings indicate that video-assisted PBL is an effective approach to improving students' understanding of complex material and motivating them to learn actively. This study provides important implications for teachers in designing interesting and student-centered learning, and emphasizes the importance of utilizing media in education.